2021
DOI: 10.1002/cam4.3721
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood pressure and BMI with bladder cancer risk and mortality in 340,000 men in three Swedish cohorts

Abstract: Background The relation between obesity, blood pressure (BP) and bladder cancer (BC) risk and mortality remains unclear, partially due to potential confounding by smoking, the strongest risk factor for BC, and not accounting for tumor stage and grade in such studies. We investigated body mass index (BMI) and BP in relation to BC risk by stage and grade, and BC‐specific mortality, including separately among never‐smokers aimed at minimizing confounding by smoking. Methods We analyzed 338,910 men from three Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Finally, the quality of 55 related studies that satisfied the inclusion criteria was assessed. Of these, 11 studies were performed in the United States [23,[26][27][28][29][30][31][32][33][34][35], 8 studies in Sweden [19,21,[36][37][38][39][40][41], 8 studies in Korea [42][43][44][45][46][47][48][49], 6 studies in the United Kingdom [20,[50][51][52][53][54], 7 studies in Taiwan [55][56][57][58][59][60][61], 2 studies each in China [62,63], Japan [64,65], Italy [66,67], Scotland [68,69], and Austria [70,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, the quality of 55 related studies that satisfied the inclusion criteria was assessed. Of these, 11 studies were performed in the United States [23,[26][27][28][29][30][31][32][33][34][35], 8 studies in Sweden [19,21,[36][37][38][39][40][41], 8 studies in Korea [42][43][44][45][46][47][48][49], 6 studies in the United Kingdom [20,[50][51][52][53][54], 7 studies in Taiwan [55][56][57][58][59][60][61], 2 studies each in China [62,63], Japan [64,65], Italy [66,67], Scotland [68,69], and Austria [70,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Statistical significance was observed for the comparison of the BMI between cases and controls (p < 0.001). By contrast, three Swedish cohorts, which included 340,000 men, indicated that BMI (hazard ratio (HR) = 1.02, 95% CI = 0.98-1.08) and systolic blood pressure (HR = 0.98, 95% CI = 0.94-1.02) showed no statistically significant associations with bladder cancer outcomes (13). A prospective pooled cohort study stated that the effects of BMI on bladder cancer varied between males and females.…”
Section: Discussionmentioning
confidence: 89%
“…After conducting a hand search specifically for studies from 2017 to 2021, 22 studies were identified. In total 47 studies were identified without the use of machine learning [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Of these 47 studies, 22 were published after 2017, as one of our focuses was to obtain more recent publications as new data have been introduced over the past 5 years since the previous meta-analysis was conducted [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the subgroup analysis of SBP and DBP per 10 mmHg, SBP showed a positive dose-dependent association with RCC ( Figure 3 ; n = 2; RR: 2.26; CI: 1.50–3.62; I 2 : 92.9%) [ 25 , 65 ] and muscle-invasive bladder cancer (MIBC) ( Figure 3 ; n = 2; RR: 1.29; CI: 1.05–1.57; I 2 : 0%) [ 31 , 32 ]. DBP also showed a positive dose-dependent association with RCC ( Figure 4 ; n = 2; RR: 2.28; CI: 1.50–3.65; I 2 : 90.8%) [ 25 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation